PERUBAHAN PERAN PEMUKA ADAT PUNYIMBANG PADA MASYARAKAT ADAT PEPADUN - Sarita, Saras; Nurbayani, Siti (Universitas Pendidikan Indonesia, 2016)
This study is about the changing role of traditional leaders called punyimbang in pepadun community. This research was conducted in the village of Terbanggi Besar, Terbanggi Besar District of Central Lampung regency. This research was motivated by the social and cultural changes taking place in society. The research is a qualitative research method of case study that compares difference conditions punyimbang role ago and today. The results of this study are firstly the social and cultural changes that occurred in the community so that the role punyimbang the first switch and always involved in every aspect of community life is starting at left, second, the factors that cause changes in this role is the modernization that began touching indigenous peoples pepadun village Terbanggi great so that people began to leave things that are traditional, third, these changes have an impact on the conflict in the community, due to the people lost figure punyimbang that exemplifies the good things that people are starting to do a lot of irregularities such as conflict between villages, spoliation, and the conflict between generations, fourth, related to the changing role of public response punyimbang happens is people still assume the existence punyimbang needed as long as there customary held by the public but does not bind as before.